First report of Dasheen mosaic virus infecting taro (Colocasia esculenta L.) from Ethiopia - Kidanemariam, Dawit B.; Macharia, M.; Harvey, Jagger J.W.; Holton, T.; Sukal, A.; James, A.P.; Harding, R.M.; Abraham, A. (Scientific Societies, 2018)
Dasheen mosaic virus (DsMV) is member of the family Potyviridae, genus Potyvirus and infects taro and other aroids wherever they grow. DsMV infection results in characteristic feathery-mottle and mosaic symptoms on leaves and can cause up to 60% production losses on taro and other edible aroids (Lebot 2009; Reyes et al. 2006). In June 2012, taro plants showing mosaic, feathery-mottle and yellowing symptoms were observed in a germplasm collection at the Areka Agricultural Research Center, Wolayita Zone, in southern Ethiopia and leaf samples were collected. The samples were initially tested for potyviruses by antigen-coated plate (ACP) ELISA using the potyvirus group PathoScreen® kit (Agdia, U.S.A.) and all eight samples tested positive. Subsequently, the samples were screened for the presence of DsMV using double antibody sandwich (DAS) ELISA (Agdia, U.S.A.), with all eight samples again testing positive. Total RNA was then extracted from the samples using the ZR RNA MiniPrepTM kit (ZYMO, U.S.A.), cDNA was synthesized using the RevertAid First Strand cDNA Synthesis Kit (Thermo Fisher Scientific, U.K.) and PCR carried out using degenerate primers NIb2F (5ʹ-GTITGYGTIGAYGAYTTYAAYAA-3ʹ) and NIb3R (5ʹ-TCIACIACIGTIGAIGGYTGNCC-3ʹ) targeting the NIb-coding region (Zheng et al. 2010). Amplicons of the expected size (350 bp) were generated from all eight samples and were cloned and sequenced. Sequencing was carried out at the SegoliP Unit at BecA-ILRI Hub (Nairobi, Kenya) and sequences were analyzed using CLC Main Workbench v6.9.2 (QIAGEN, U.S.A). The eight sequences (deposited in GenBank as accession nos. MG709254 - MG709261) shared 86 to 100% nucleotide identity. BLAST analysis showed a maximum of 88 and 96% identity at the nucleotide and amino acid levels, respectively, to DsMV isolate SdP from China (GenBank accession no. JX083210) infecting the aroid Pinellia pedatisecta. To the best of our knowledge this is the first report of DsMV infecting taro in Ethiopia. Taro is widely grown and is an important staple food crop in south Ethiopia. The presence of DsMV presents a serious threat to taro production and further work is needed to determine the geographic distribution, incidence and yield losses associated with DsMV infection in taro growing areas in Ethiopia.